A simple approach based on intron length polymorphism (ILP) for chromosomal localization of Gene WAG-2 - Wei, Shuhong; Peng, Zhengsong; Yang, Zaijun (The Indian Journal of Genetics and Plant Breeding, 2016)
Intron polymorphism can be used to develop potential intron polymorphism (PIP) markers. Intron length polymorphism (ILP) is one of the most easily identified PIP markers. WAG-2, a class C MADS-box gene, had been isolated from the wheat expressed sequence tag (EST) database. Rich polymorphisms, such as intron allele variation, and length polymorphism occur in WAG-2 gene introns. Especially, a significant length polymorphism is shared by intron IV. In present study, based on intron IV length polymorphism, using wheat nullisomic-tetrasomic (NT) and ditelosomic (DT) lines, a pair of ILP primers were designed in exons flanking introns IV and the WAG-2 gene was located on the short arm of homologous group 3 chromosome in the wheat genome. The gene location approach by using ILP markers combining with aneuploidy is convenient, reliable, specific, codominant, and stable. It is expected that ILP markers will play important roles in the genetic studies and breeding of wheat